Determinación de la concentración de nitrógeno orgánico, fósforo y potasio a partir de los residuos orgánicos generados en el mercado central de la ciudad de Moyobamba - Rojas Torres, Odilardo (2015)
Under this scenario, the present work is the result of a detailed investigation to comply with our objectives and give a response to our approach to the problem. In this report can be find valuable information in regard to the components, volumes, density, PPV; we also have at our disposal performance data of the compost produced by the so lid waste, and finally we have to reach the of nutrients percentage organic nitrogen, phosphorus and potassium that we find in the compost. Coming to the conclusion that: The segregation is done by sectors, in this sense the food sector had 23 types of organic waste; the fruit- juice stands had 19 types of organic waste and finally the vegetable sector had 34 types of organic waste, the three together they made a total of 1594. 84 kg of organic residues. With an average volume of 0.57 m3, with a total average density of 3037.61 kg/m3, with a production post-sale 2.72 kg/post/day for the food sector, a 4.42 kg/post/day for the fruit sector - juice stands, and a 3.50 kg/post/day for the sector vegetables. To determine the performance food sector obtained 50.75 kg of compost, a yield of 9.50%; for the sector of fruits-juice stands of 8.67 kg of compost, with a yield of 2.45%; in the sector of vegetables is of 18.24 kg, with a loss in the process of 426.05 kg and a yield of3.82 %; and the witness hada final product of 15.35kg compost, with a yield of 5.70%. The analysis ofthe concentrations is in average in Nitrogen ofthe sector food was 2.14 %, ofthe sector fruits- juice stands it was 3.05 %, ofthe sector Vegetables it is 2.07% and the witness was 2.59 %. The average in phosphorus in the sector food was 0,441 %, ofthe sector fruits- juice stands 0.437 %, ofthe sector Vegetables he is a 0.514% and the witness 0.31 %. The average ofPotassium ofthe sector food was 3.77 %, ofthe sector fruits- juice stands it was 2.37 %, ofthe sector vegetables it was 3.86 %, and the witness was 3.97 %. Key words: organic solid waste which, segregation.